IMPLEMENTASI PENGGUNAAN LKPD BERBASIS LITERASI UNTUK MELATIH KETERAMPILAN BERPIKIR KRITIS PADA PEMBELAJARAN MATEMATIKA KELAS II SDN PANDEANLAMPER 01: Penelitian Tindakan Kelas - N Ngatmi; Norma Yanti Ngatmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The background that drives this research is that students' reading abilities are at a proficient level, meaning that students still need help to improve their ability to master concepts and develop independently the knowledge skills they have. The aim to be achieved in this research is to determine the implementation of using literacy-based LKPD to train critical thinking skills in mathematics learning. This type of research is quantitative research in the form of preexperimental design in the form of One-Group-Pretest-Posttest Design. The population in this study were class II students at SDN Pandeanlamper 01. The samples taken were all class II students at SDN Pandeanlamper 01, totaling 28 students. The sampling technique used in this research is non-probability sampling with saturated sampling type. This research instrument uses interviews, tests, observations and documentation. The data analysis used consists of normality tests, homogeneity tests, and hypothesis tests. The research results showed that the average pretest score for critical thinking skills with the posttest score increased by 20.36. This shows that the use of literacy-based LKPD has experienced a fairly high increase. This is supported by interviews conducted with students who understand that learning mathematics prefers to read. With the use of literacy-based LKPD, students are happier and can understand the content of the material provided.